IMPROVING ORTHODONTIC AND ORTHOPEDIC CARE FOR PATIENTS WITH EXTRAORAL PATHOLOGIES WHO HAVE UNDERGONE RADIATION THERAPY (Ustozlar uchun, 2026)
Subject. To improve the quality of life for patients who have undergone extensive oncological surgeries in the maxillofacial region, a step-by-step prosthetic approach is implemented. The development of materials that closely mimic living tissues has led to significant advancements in facial prosthetics over recent decades. Siloxanes are among such prominent materials. Experimental and clinical studies conducted by the Central Research Institute of Prosthetics have demonstrated that silicone prostheses are biologically inert, maintain their shape, and do not lose their elasticity or durability. Currently, rapid prototyping and 3D modeling technologies are being actively integrated into this field.